2009
DOI: 10.1182/blood-2008-05-154773
|View full text |Cite
|
Sign up to set email alerts
|

Basophil effector function and homeostasis during helminth infection

Abstract: IntroductionBasophil development and function is poorly understood, although this rare cell type was identified by Paul Ehrlich in 1879. 1 Basophils constitute less than 0.3% of leukocytes in the peripheral blood. They are functionally closely related to mast cells, since both cell types express the high-affinity receptor for IgE and produce similar effector molecules, including histamine, lipid mediators (eg, leukotrienes and prostaglandins), serine proteases, and interleukins (eg, IL-4, IL-13, and IL-6). 2 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
163
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(169 citation statements)
references
References 43 publications
4
163
0
2
Order By: Relevance
“…Mice were infected with L3 larvae of N. brasiliensis, as described previously (16). Mice were reinfected 4-5 wk after the first infection for analysis of the memory response.…”
Section: N Brasiliensis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were infected with L3 larvae of N. brasiliensis, as described previously (16). Mice were reinfected 4-5 wk after the first infection for analysis of the memory response.…”
Section: N Brasiliensis Infectionmentioning
confidence: 99%
“…Furthermore, several recent publications demonstrated that basophils are important APCs driving the differentiation of Th2 cells in allergy models (13)(14)(15). Recently, we demonstrated that basophils contribute to the efficient expulsion of N. brasiliensis after a primary infection in the absence of Th2 cells (16). In addition, it was shown that basophils are equally important for resolving Trichuris muris infection (14).…”
mentioning
confidence: 99%
“…Like mast cells, the basophils role in the immune system has been mainly focused on its role in acute models of allergic reactions or on chronic models of parasitic infection where they appear to be important upon a second infection with the parasite [46]. However, if the basophil functions as an immunomodulatory cell, one might predict that there would be instances where the basophil might play an important role in immune diseases other than allergic disease.…”
Section: The Basophils Beyond Allergymentioning
confidence: 99%
“…In this issue, Ohnmacht and Voehringer address the development and lifespan of basophils and further investigate their role in helminth infections. 5 In addressing these issues, they first identified the expression of the Thy1 antigen on the surface of IL-4 -expressing cells, which were defined by expression of green fluorescent protein in the 4get transgenic mouse. The basophils were distinguished from the other IL-4 ϩ , FceRI ϩ cell type, the mast cell, by the lack of the mast cell marker c-kit.…”
Section: The Expanding Universe Of the Basophil ---------------------mentioning
confidence: 99%
“…Advances in liquid chromatography-tandem mass spectrometry-driven proteomics have shifted the paradigm of translational cancer research that enables fast and reliable large scale study of proteins involved in many disease models. 4 It follows that identifying the ALK-regulated proteome 5,6 and phosphoproteome would lead to key insights into the signaling pathways important for the pathogenesis of ALCL.…”
mentioning
confidence: 99%